Development of biocatalysts immobilized on coal ash-derived Ni-zeolite for facilitating 4-chlorophenol degradation. (July 2020) - Lim, Yejee; Yu, Jimin; Park, Sungyoon; Kim, Minsoo; Chen, Siyu; Bakri, Nurul Aziemah Binti; Sabri, Nur Izzati Auni Binti Mohd; Bae, Sungjun; Kim, Han S.
Graphical abstract: Highlights: Coal fly ash-derived Ni-zeolite was developed as an enzyme support. The enzyme immobilization yield was 77.5%. Immobilized CphC-I catalyzes the initial step of 4-CP biodegradation. The activity of immobilized CphC-I was 7.98 U/g Ni-zeolite. vmax  = 0.20 mM/min, KM  = 0.44 mM, and kcat / KM  = 0.02 mM −1. min −1 . Abstract: A new type of biocatalyst was developed to facilitate the biochemical decomposition of 4-chlorophenol (4-CP) in this study. Oxydoreductases that catalyze the initial steps of 4-CP biodegradation were immobilized on a synthetic inorganic enzyme support. Type-X zeolite, a high-surface area support, was synthesized from coal fly ash, on which nickel ions were plated by impregnation (Ni-zeolite), followed by the effective immobilization (77.5% immobilization yield) of recombinant monooxygenase (CphC-I), dioxygenase (CphA-I), and flavin reductase (Fre) isolated from Pseudarthrobacter chlorophenolicus A6 and Escherichia coli K-12, respectively. The retained catalytic activity of the enzymes immobilized on Ni-zeolite was as high as 64% of the value for the corresponding free enzymes. The Michaelis–Menten kinetic parameters vmax and KM of the immobilized enzymes were determined to be 0.20 mM·min −1 and 0.44 mM, respectively. These results are expected to provide useful information with respect to the development of novel enzymatic treatments for phenolic hydrocarbon contaminants.